Pemberdayaan Penjual Dan Petani Salak Dalam Bidang Pengolahan Limbah Salak Busuk Menjadi Bioethanol - Siboro, Impol; Yuliana, Lina; Setyawati, Nur Falah; wahyuni, Sri (EUNOIA, 2023)
The method of this research activity is in the form of community training carried out on Jl. Soekarno Hatta KM 23, Karang Joang village, North Balikpapan sub-district. With this activity, the salak farming community will take advantage of the potential for salak waste to be dumped on the side of the garden, left to rot, then turned into compost. However, with this activity, farmers use it to produce bioethanol. The head of the RT at Kilometer 23 Karang Joang appreciated this activity which introduced the salak waste management program. It is hoped that this program will be immediately implemented by its residents, the majority of whom are salak farmers.